INTEGRASI PEMBELAJARAN BERBASIS TEKNOLOGI MELALUI PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN SEKOLAH DASAR - Santi Eka Putri; Elliza Nofri Yenny; Detri; Erman Har; Karmila Suryani (STKIP Subang, 2026)
The development of information technology has driven the need for innovation in elementary school learning so that the learning process remains relevant to the demands of the 21st century. One effort that can be made is to integrate technology-based learning with a scientific approach. This study aims to describe and analyze the integration of technology-based learning through a scientific approach in elementary school learning at SDN 26 Lubuk Alung. This study uses a qualitative approach with a descriptive research type. The research subjects include classroom teachers, students, and the principal. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was conducted qualitatively through data reduction, data presentation, and conclusion drawing. The results showed that the integration of technology-based learning through a scientific approach was able to create more active, interactive, and meaningful learning. The use of technology at each stage of the scientific approach can increase student engagement, encourage critical thinking skills, and strengthen the role of teachers as learning facilitators. Although there were several obstacles in its implementation, such as differences in students' abilities to utilize technology, teachers were able to make adjustments so that learning remained effective. This study concluded that the integration of technology-based learning through a scientific approach is a relevant and effective strategy for improving the quality of learning in elementary schools